THE EFFECT OF FINANCIAL RATIO AND CORPORATE GOVERNANCE MECHANISMS ON THE FINANCIAL DISTRESS IN THE INDONESIA STOCK EXCHANGE - Titik Setyaningsih; Tri Gunarsih (Journal of Applied Economics in Developing Countries, 2018)
The main objective of this research is to examine the influence of financial ratios (Current Ratio, Debt to Equity Ratio, Debt to Assets Ratio, Return on Asset) and governing mechanism (institutional ownership) to the financial distress of the non financial companies listed in Indonesian Stock Exchange. The data used in this research are secondary data. Samples in this research are non financial companies listed during 2012-2016. The hypotheses are tested by running logistic regression analysis. The dependent variable is financial distress proxied by earning per share. The results show that institutional ownership influenced financial distress. While Current Ratio, Debt to Equity Ratio, Debt To Assets Ratio, and Return On Asset did not influenced the financial distress.Keywords: Financial Ratio, Institutional Ownership, Financial Distress